Efficient AntiMycolata Agents by Increasing the Lipophilicity of Known Antibiotics through Multicomponent Reactions - Angela Trejo; Carme Masdeu; Irene Serrano-Pérez; Marina Pedrola; Narcís Juanola; Ouldouz Ghashghaei; Guadalupe Jiménez-Galisteo; Rodolfo Lavilla; Francisco Palacios; Concepción Alonso; Miguel Viñas (MDPI AG, 2023)
New antibiotic agents were prepared using Povarov and Ugi multicomponent reactions upon the known drugs sulfadoxine and dapsone. The prepared derivatives, with increased lipophilicity, showed improved efficiency against Mycolata bacteria. Microbiological guidance for medicinal chemistry is a powerful tool to design new and effective antimicrobials. In this case, the readily synthesized compounds open new possibilities in the search for antimicrobials active on mycolic acid-containing bacteria.